Perceived determinants of alcohol usage among male students in tertiary institutions: The way out for health and educational development: A case study of College of Education, Ikere-Ekiti (2010)
This is paper examines the determinants and extent of alcohol usage among male students in tertiary institutions, a case study of College of Education, Ikere -Ekiti. The subjects for the study consist of six hundred students randomly selected from the five schools in the institution. The instrument for the study was a self constructed and administered questionnaire. The data collected were analyzed using descriptive statistics of percentages and non parametric statistics of chi-square at 0.05 level of significance. It was found out that alcohol usage was prevalent among students. The students who drink started from the age 16 years which shows that adolescent age were found to significantly influence drinking habits of students. Parental influence, peer group influence, readily availability of products, as well as advertisement on print and news medial influence alcoholic usage of the students. It was also found out that students were not aware of the harmful effects of alcohol usage on their health. The paper recommended that activities such as symposium, lecture, seminar and debate should be carried out in all schools and colleges to create awareness on the dangers of drinking alcohol. Alcohol education should also be incorporated into the school curriculum and should be taught as a subject/course by health education expert.